Characterizing azobenzene disperse dyes in commercial mixtures and children's polyester clothing. (15th October 2021) - Overdahl, Kirsten E.; Gooden, David; Bobay, Benjamin; Getzinger, Gordon J.; Stapleton, Heather M.; Ferguson, P. Lee
Abstract: Azobenzene disperse dyes are the fastest-growing class of dyestuffs, yet little is known about dye occurrences, sources, and transformations; azo dyes are also underrepresented in chemical standard catalogs, molecular databases, and mass spectral libraries. Many azo dyes are known to have sensitization, mutagenic, and carcinogenic properties. To fill these knowledge gaps, azo dyes were purified from dyestuffs by Soxhlet extraction and flash chromatography and characterized using ultra-high-performance liquid chromatography (UHPLC) coupled to a high resolution Orbitrap Fusion Lumos mass spectrometer operated in positive electrospray ionization mode, as well as by 1 H and 13 C NMR. Data were analyzed to identify likely chemical formulas and structures using a weight-of-evidence approach with multiple open-source, in silico computational mass spectrometry tools. Nineteen total azobenzene dyes were detected in dyestuffs via a non-targeted analysis approach; the azobenzene dyes Disperse Blue 79:1, Disperse Blue 183:1, Disperse Orange 44, Disperse Orange 73, Disperse Red 50, Disperse Red 73, and Disperse Red 354 were purified from raw dyestuffs. Samples of children's polyester clothing were then analyzed likewise. In clothing, 21 azobenzene disperse dyes were detected, 12 of which were confirmed and quantified via reference standards. Individual dyes in apparel were quantified at concentrations up to 9230 μg dye/g shirt, with geometric means ranging 7.91–300 μg dye/g shirt. Total dye load in apparel was quantified at up to 11, 430 μg dye/g shirt. This research supported the development of reference standards and library mass spectra for azobenzene disperse dyes previously absent from standard and spectral libraries. By analyzing the scope and quantities of azo dyes in children's polyester apparel, this study will facilitate a more robust understanding of sources of these potentially allergenic and mutagenic compounds. Graphical abstract: Image 1 Highlights: Nineteen total azobenzene dyes were detected in dyestuffs via non-target analysis. In children's polyester clothing, 21 azobenzene dyes were detected. 12 azo dyes were quantified in clothing at levels up to 9230 μg dye/g shirt. Total dye load in apparel was quantified at up to 11, 430 μg dye/g shirt.